Models of computation in context 7th Conference on Computability in Europe, CiE 2011, Sofia, Bulgaria, June 27 - July 2, 2011. Proceedings - Conference on Computability in Europe 2011 Sofia, Bulgaria); Löwe, Benedikt; Normann, Dag.; Soskov, Ivan.; Soskova, Alexandra; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 7th Conference on Computability in Europe, CiE 2011, held in Sofia, Bulgaria, in June/July 2011.The 22 revised papers presented together with 11 invited lectures were carefully reviewed and selected with an acceptance rate of under 40%. The papers cover the topics computability in analysis, algebra, and geometry; classical computability theory; natural computing; relations between the physical world and formal models of computability; theory of transfinite computations; and computational linguistics.
Electronic reproduction.
Keywords: Computable functions -- Congresses; Electronic books